An improved pre-lithiation of graphite anodes using through-holed cathode and anode electrodes in a laminated lithium ion battery. (20th November 2019) - Watanabe, Tatsuya; Tsuda, Takashi; Ando, Nobuo; Nakamura, Susumu; Hayashi, Narumi; Soma, Naohiko; Gunji, Takao; Ohsaka, Takeo; Matsumoto, Futoshi
Abstract: In order to actually compensate "an irreversible capacity ( i.e., an active lithium loss) ˮ usually observed at the 1st charging/discharging cycle of lithium ion batteries (LIBs), e.g., caused by a solid-electrolyte interphase (SEI) formation, a so-called pre-lithiation was applied to the graphite anodes of the laminated cell composed of three graphite anodes and three LFP (lithium iron phosphate) cathodes which were through-holed with the hole diameter of 20, 100 or 200 μm like the squares of a "Go-board". The pre-lithiation was carried out (keeping an appropriate pre-lithiation charge amount) firstly by directly contacting the anodes with Li metal, which was previously introduced in the cell, to intercalate Li + ions to them and then conducting the capacity balancing among the Li + -intercalated anodes by contacting them for a various period of time. It was found that in the cell composed of the through-holed anodes and cathodes with a given hole diameter the irreversible capacity can be significantly reduced by appropriately choosing the pre-lithiation charge amount and the capacity balancing time. Typically, in the anodes (the hole diameter: 20 μm) with the total capacity of 35 mAh, when the pre-lithiation charge amount was 3 mAh and the capacity balancing time was 12 h, no irreversible capacity could be observed actually, i.e., the 1st charge capacity was close to 100% and the expected stable charge/discharge capacities were obtained with the capacity retention of almost 100% in the continuous charge/discharge cycle. The results obtained demonstrate that the pre-lithiation of LIBs can be significantly improved using through-holed anodes and cathodes. Graphical abstract: Image 1